2010
DOI: 10.1186/1479-7364-4-6-375
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene polymorphisms -786T >C and 894G >T in coronary artery bypass graft surgery patients

Abstract: Polymorphisms in the endothelial nitric oxide synthase (eNOS) gene (-786T >C and 894G >T) enhance endo-thelial dysfunction and have been studied in relation to coronary artery disease (CAD). In the present study, we examined the association of the above polymorphisms with CAD, as well as with myocardial infarction (MI), hypertension, diabetes and smoking in CAD patients. Study subjects consisted of 154 consecutive coronary artery bypass graft (CABG) patients and 155 non-CAD controls. eNOS -786T >C and 894G >T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Two common polymorphisms(- 786T>C and 894G>T) will be assessed with a 5′-allele discrimination PCR assay using primer sequences previously described by our group and others. 19,20 Both polymorphisms impair eNOS synthesis of endogenous NO, impair endothelial-induced vascular smooth muscle relaxation, increase red cell fragility and increase the risk of PE in Caucasians and Asians. 20-22 The hypothesis is that patients with these variations will have improved response to inhaled NO.…”
Section: Trial Conduct and Registrationsmentioning
confidence: 99%
“…Two common polymorphisms(- 786T>C and 894G>T) will be assessed with a 5′-allele discrimination PCR assay using primer sequences previously described by our group and others. 19,20 Both polymorphisms impair eNOS synthesis of endogenous NO, impair endothelial-induced vascular smooth muscle relaxation, increase red cell fragility and increase the risk of PE in Caucasians and Asians. 20-22 The hypothesis is that patients with these variations will have improved response to inhaled NO.…”
Section: Trial Conduct and Registrationsmentioning
confidence: 99%
“…Several eNOS genomic polymorphisms have been described in association with pathological cardiovascular conditions; among them is the exon 7 G894T eNOS polymorphism, leading to amino acid substitution at position 298 (conversion of glutamate to aspartate) [6]. The clinical significance of the G894T eNOS polymorphism in humans was assessed in multiple studies, and significant association was found between this eNOS polymorphism and various cardiovascular conditions, including vasospastic angina, hypertension, and carotid and coronary atherosclerosis [7][8][9][10][11][12][13][14]. Several recent meta-analyses concluded that eNOS G894T polymorphism may increase the risk of developing thrombotic diseases and may play an important role in the development of hypertension, ischemic stroke and coronary heart disease [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…This result is similar to that of Piccoli et al (2012), where they analyzed a South-Brazilian population and found a greater prevalence of the TC genotype in patients with acute coronary syndrome (ACS) and controls. Ragia et al (2010) found that the TC genotype (55.2% in the case group and 54.8% in control) had a higher prevalence concerning the other genotypes and they also did not find a statistically significant difference for patients who underwent myocardial revascularization surgery. A study conducted by Ghilardi et al (2002) in Italian patients found that the genotypic distribution in the controls was 54 TT (41%), 61 CT (46%), and 18 CC (13%), corroborating the studies in the present research.…”
Section: Discussionmentioning
confidence: 79%